Abuso nel diritto civile e nel diritto tributario, e l’abuso del processo – Parte Prima - Luigi Di Prisco (Aequitas Magazine)
This study succinctly illustrates the concept of abuse of rights within civil and tax law, with an evolutionary reconstruction from its origins to recent applications in procedural law, where it has assumed a well-defined position with a regulatory framework of a sanctioning nature, aimed at reducing litigation by repressing the abuse of process. The work is divided into three parts (I: The abuse in civil law; II: The abuse in tax law; III: The abuse of process) for easier reading and understanding.